New Subjectivities: Maasai Schoolgirlhood as Light and (Girl Effects) Logic: When the Light Is Fire: Maasai Schoolgirls in Contemporary Kenya. Issue 2 (1st June 2021) - Unknown
Abstract : Heather D. Switzer. 2018. When the Light Is Fire: Maasai Schoolgirls in Contemporary Kenya . Urbana, IL: University of Illinois Press.